Universal Health Coverage - The Critical Importance of Global Solidarity and Good Governance; Comment on "Ethical Perspective: Five Unacceptable Trade-offs on the Path to Universal Health Coverage" - Andreas A. Reis (Kerman University of Medical Sciences, 2016)
This article provides a commentary to Ole Norheim' s editorial entitled "Ethical perspective: Five unacceptable trade-offs on the path to universal health coverage." It reinforces its message that an inclusive, participatory process is essential for ethical decision-making and underlines the crucial importance of good governance in setting fair priorities in healthcare. Solidarity on both national and international levels is needed to make progress towards the goal of universal health coverage (UHC).